Perbedaan Skor Domain Health Promoting Lifestyle Antar Kategori Persentase Lemak Tubuh - Ahmad Rizki Akbar Dwiputra; Rizki Suganda Prawiradilaga; Samsudin Surialaga (UNISBA Press, 2024)
Abstract. Body fat percentage (%BF) is a primary concern in the context of health and lifestyle. Excessive body fat can lead to serious health issues and contribute to the risk of chronic diseases, while the pressure to achieve an 'ideal' body can negatively impact an individual's psychological aspects. This study aims to observe differences in the health promoting lifestyle profile-2 (HPLP-II) domains across %BF categories among students of the Faculty of Medicine. This research employed an observational analytic quantitative method with a cross-sectional approach. The study involved 96 active medical faculty students willing to measure their %BF and complete the questionnaire as inclusion criteria. Exclusion criteria included incomplete questionnaire responses and a history of congenital diseases. Sampling was done using purposive sampling technique. Body fat percentage was measured using bioimpedance analysis and categorized into low, normal, overweight, and obesity. The health-promoting lifestyle profile domains were assessed using the HPLP-II questionnaire, which includes Health Responsibility (HR), Physical Activity (PA), Nutrition (N), Spiritual Growth (SG), Interpersonal Relationship (IR), and Stress Management (SM) domains. The results were analyzed using one-way ANOVA. The study found no significant differences across %BF categories in all HPLP domains: HR (p=0.964), PA (p=0.532), N (p=0.616), SG (p=0.547), IR (p=0.547), and SM (p=0.376). The lack of significant differences in this study may be due to other factors influencing %BF, such as genetics, metabolism, and culture. Abstrak. Persentase lemak tubuh (%LT) menjadi perhatian utama dalam konteks kesehatan dan gaya hidup. Lemak tubuh yang berlebihan dapat menyebabkan masalah kesehatan serius dan berkontribusi pada risiko penyakit kronis, sementara tekanan untuk mencapai tubuh